Solid phase transformation of Carbamazepine-Saccharin (CBZ-SAC) co-crystal - Nur Aida, Zakiriah (2013)
A research was conducted on the solid phase transformation and stability of carbamazepine-saccharin co-crystal. Pharmaceutical co-crystal is one of the potential methods for improving the bioavailibity of drugs with low aqueous solubility. Thus, the purpose of this research is to determine the stable region of carbamazepine-saccharin (CBZ-SAC) co-crystal formation by using solution based method. In this method, three technique are used which are cooling crystallization, solvent evaporation and slurry, to prepare the chemical and use ethanol as a solvent. Different mol ratio of CBZ and SAC are being tested, in order to study CBZ-SAC cocrystal formation. Physical characterizations of the co-crystal are being characterized by differential scanning calorimetry and research microscope. Overall as the concentration of saccharin increase the melting point increase and will lead to poor solubility but mostly the melting point of co-crystal resulting in lower melting point. From this research can be concluded that CBZ-SAC co-crystal can form two forms which are plate-like and needle like. Varying the mol of carbamazepine and used different solvents could be used for further studies to see the difference trending.